1991
DOI: 10.1038/bjc.1991.201
|View full text |Cite
|
Sign up to set email alerts
|

Hetergeneous tumour response to photodynamic therapy assessed by in vivo localised 31P NMR spectroscopy

Abstract: We report here initial results using localised in vivo 31P

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…It is supposed that, for many types of tumors, response to irradiation or chemotherapy appears to show the reversal of the trends seen in untreated tumor progression. Some other therapeutic modalities, notably hyperthermia ) and photodynamic therapy (Ceckler et al 1991), however, show the opposite response : acidic shift, decrease of NTP • PCr and increase of Pi • PME levels. It is suggested that those changes in 31P-MRS following irradiation or chemotherapy are due to the metabolic activation in tumor tissue caused by reoxygenation (Gohda et al 1990; Kimura et al 1992) or due to decrease in demand for high energy phosphate in the damaged cells following treatment, as the cellular energy supply is sufficient for the metabolic needs of the tumor (Steen 1989(Steen , 1991.…”
Section: Discussionmentioning
confidence: 99%
“…It is supposed that, for many types of tumors, response to irradiation or chemotherapy appears to show the reversal of the trends seen in untreated tumor progression. Some other therapeutic modalities, notably hyperthermia ) and photodynamic therapy (Ceckler et al 1991), however, show the opposite response : acidic shift, decrease of NTP • PCr and increase of Pi • PME levels. It is suggested that those changes in 31P-MRS following irradiation or chemotherapy are due to the metabolic activation in tumor tissue caused by reoxygenation (Gohda et al 1990; Kimura et al 1992) or due to decrease in demand for high energy phosphate in the damaged cells following treatment, as the cellular energy supply is sufficient for the metabolic needs of the tumor (Steen 1989(Steen , 1991.…”
Section: Discussionmentioning
confidence: 99%
“…The pH of the R3230AC tumour is approximately 7.15, as determined by Ceckler et al (1991) using 31 P NMR spectroscopy. The Hill coefficient, n and the p 50 corresponding to this pH are 2.46 and 33.7 torr, respectively (Zwart et al, 1982(Zwart et al, , 1984.…”
Section: Figurementioning
confidence: 99%
“…Within each of these subpopulations, there is a trend toward a larger carbogen-induced change for tumours with lower initial saturation. Using a pH of 7.15 for the R3230AC tumour, which has been determined by Ceckler et al (1991) from 31 P NMR spectroscopy measurements, and the Hill parameters n (2.46) and p 50 (33.7 torr) corresponding to this pH (Zwart et al, 1982(Zwart et al, , 1984, we fit an expression of the form to the data in Figure 7 to find the average change in blood pO 2 (∆pO 2 ) induced by carbogen. The derivation of this equation is presented in the Appendix.…”
Section: Figurementioning
confidence: 99%
“…Gadolinium diethylenetriamene pentaacetate (DTPA) contrast-enhanced MRI was used to assess the boundary of PDT-induced tissue necrosis in a canine model [23] and in human patients [24]. Second, in vivo 31 P nuclear magnetic resonance (NMR) spectroscopy has been used to monitor tumor metabolic status before and after the treatment of RIF-1 tumors [25,26] and mammary carcinoma [27][28][29][30]. NMR data analysis revealed significant differences in the time course of changes in high energy phosphate levels in response to combined hyperthermia and photodynamic therapies [29].…”
Section: Introductionmentioning
confidence: 99%